AN EFFICIENT PRESENTATION FOR THE GROUP SL (2,121) (Journal of Sciences, Islamic Republic of Iran)
In this paper we give a 2-generator 2-relation presentation for the group SL(2,121). This proves that SL(2,121), the covering group of PSL(2,121), is efficient